Clinical significance of nuclear p53 protein accumulation in bladder cancer - (:unkn) unknown (My University, 1999)
Objectives: To investigate the correlation of nuclear p53 accumulation with disease outcome in a cohort of patients with transitional cell carcinoma of the bladder. Methods: A total of 90 patients (11 female, 79 male) with transitional cell carcinoma of the bladder were included in this study. Tumour samples from the primary turnout were analysed by immunohistochemistry for nuclear accumulation of p53 protein. Outcome of each patient was recorded and investigated for a possible relation with p53 status. Results: Nuclear p53 deposition was determined in 22 specimens. The nuclear p53 deposition was seen in less than 20% of the nuclei examined in 13 and more than 20% in 9 cases. No stromal staining was observed. Nuclear p53 deposition was present in 15.2% (7/46) of grade 2 tumours, and 34% (15/44) of grade 3 tumours (p=0.037). Stage distribution revealed 15.5% (5/33) positivity in stage pTa, 25.8% (8/31) in pT1 and 34% (9/26) in stage pT2-3 tumours. Tumours with p53 nuclear accumulation had a higher rate of recurrence and progression and shorter survival. Conclusion: Results of the current study indicate p53 as an important factor in determination of biological behaviour of bladder cancer.